A transnational cooperation for sustainable use and management of non-native trees in urban, peri-urban and forest ecosystems in the Alpine region (ALPTREES) - Katharina Lapin; Anja Bindewald; Florian Kraxner; Aleksander Marinšek; Nicola La Porta; Reneema Hazarika; Debojyoti Chakraborty; Janine Oettel; Frederic Berger; Patricia Detry; Gordana Kolesaric; Darja Baric; et al. (Research Ideas and Outcomes, 2020)
The expected benefits and potential risks of non-native tree species (NNT) to European geographic regions have polarized the opinions of experts and citizens. Benefits include climate change (CC) mitigation and adaptation, contributions to bioeconomy, urban and peri-urban green infrastructure and mitigation of natural hazards. However, NNT may become invasive and thus may pose risks to native biodiversity, ecosystem functioning or socio-economy. In critical and vulnerable ecosystems such as the Alpine Space (AS), such risks and benefits must be carefully considered before management decisions are made. Experiences in the management of NNT in urban areas, peri-urban, rural territories and forests are often region- or city-specific and rarely shared. Given the challenges in NNT management with respect to both benefits and risks, an European transnational approach is needed to qualify the role of NNT in future AS ecosystems. The objective is to provide a transnational strategy for a responsible use and sustainable management of NNT in the AS with the help of an integrated Decision Support System. The project fits within the context of national and regional site-derived policy aiming at protecting and enhancing biodiversity to ensure ecological connectivity and cultural resources while maintaining a high level of resilience and ecosystem services across the AS. Implementation activities of the ALPTREES project includedeveloping a comprehensive database on NNT,projecting the current and potential distribution of NNT in the AS under CC scenariosdetermining their invasive potential andanalyzing the different ecosystem services provided by NNT to assess the tradeoffs between risks and benefits.ALPTREES will formulate management recommendations for NNT under different climate and economic scenarios based on experience from sample plots combined with model projections, citizen science, and multiple stakeholder meetings. With the help of policy briefs, a handbook of lessons learned, transnational pilot actions for best management practices, and an inter-active online Decision Support System a close stakeholder interaction and -benefit will be ensured Another innovative output of the project is the Open ALPTREES Knowledge Hub, that will support the transnational and interdisciplinary knowledge transfer.